Free vascularised fibular grafts in orthopaedics - Bumbasirevic, Marko; Stevanovic, Milan; Bumbasirevic, Vesna; Lesic, Aleksandar; Atkinson, Henry D. E. (International orthopaedics, 2014)
Bony defects caused by trauma, tumors, infection or congenital anomalies can present a significant surgical challenge. Free vascularised fibular bone grafts (FVFGs) have proven to be extremely effective in managing larger defects (longer than 6 cm) where other conventional grafts have failed. FVFGs also have a role in the treatment of avascular necrosis (AVN) of the femoral head, failed spinal fusions and complex arthrodeses. Due to the fact that they have their own blood supply, FVFGs are effective even in cases where there is poor vascularity at the recipient site, such as in infection and following radiotherapy. This article discusses the versatility of the FVFG and its successful application to a variety of different pathologies. It also covers the applied anatomy, indications, operative techniques, complications and donor-site morbidity. Though technically challenging and demanding, the FVFG is an extremely useful salvage option and can facilitate limb reconstruction in the most complex of cases.